Role of Union Government in Indian Federal System to Establish Constitutional Machinery in States: New Dimensions of Constitutionalism with Special Reference to Manipur Violence - Sudarshan Verma (AG Volumes, 2026)
The Constitution of India is supreme law of the nation. It is both a legal and social document which provides the government machinery for the governance of the country. The objective of the Constitution is to ensure good governance in the country, where, all the organs of the government and their powers, duties and liabilities are subject to the provisions of the Constitution. These provisions also assist the government in carrying out all of its functions related to welfare of the people, maintain law and order, peace and tranquility in the society. The Constitutional framework mandates that the State as a welfare state is to protect the fundamental rights of its citizens, which could not be possible in a lawless state. Constitution makers were very much concerned about the governance of the country. Therefore, they made the provisions in the constitution to tackle situations of lawlessness if it occurred in a state. Every Government, be it the Union or State, is subject to provision of the Constitution. Action of the government in violation of the provisions of the Constitution, are subject to judicial review and liable to be declared ultra-virus by the judiciary. The chapter discusses the comprehensive constitutional framework of India’s federal structure and analyses the delicate balance cast by it between federal and unitary principles. It analyses the duty of the federal government in protecting the federal structure especially during various constitutionally envisioned forms of emergency experienced in the nation. This chapter focuses on the constitutionality and challenges faced by declaration of President rule in case of an emergency in a State in the past. This discussion was brought to the fore yet again when the State of Manipur was brought to a halt on account of severe unrest. The chapter discusses the internal disturbance that riddled Manipur and evaluates the validity and reasons behind the decision of the Union Government in not imposing President’s rule in this case.